Synthesis, Structures, and Antibacterial Activities of Four Similar 1D Metal‐organic Polymers with Different Metal Ions. Issue 11 (22nd June 2020) - Wang, Yufei; Khan, Misbha Rafiq; Niu, Xiaoge; Zhang, Wenjing; Li, Yulin; Li, Bohan; Hao, Yaping; Li, Jinpeng; Liu, Zhongyi
Abstract : Four similar 1D metal‐organic polymers [Cd(impc)2 (H2 O)2 ] n (1 ), [Co(impc)2 (H2 O)2 ] n (2 ), [Mn(impc)2 (H2 O)2 ] n (3 ), and [Cu(impc)2 ]· [jy2H2 O n (4 ) based on an asymmetric 5‐(1H‐imidazole‐l‐yl)‐3‐pyridinecarboxylic acid (Himpc) were prepared hydrothermally and structurally characterized. According to the frontier molecular orbital (FMOs) calculations, the photoluminescence of 1 should be assigned as the n→π* transition. The antibacterial properties of 1 –4 were studied. 1 exhibited good antibacterial activities towards B. subtilis and S. aureus with the smallest MIC value of 2 μg· mL –1 . Compared with Co II, Mn II and Cu II ions, the polymer with Cd II ion has the better antibacterial activity. Our work preliminarily reveals that the metal ions also have different influences on antibacterial activities of complexes. Abstract :